(untitled) (Communications in Computational Physics, 2010)
Borehole acoustic logging-while-drilling (LWD) for formation evaluation has become an indispensable part of hydrocarbon reservoir assessment [F. Cittá, C. Russell, R. Deady and D. Hinz, The Leading Edge, 23 (2004), pp. 566-573]. However, the detection of acoustic formation arrivals over tool mode contamination has been a challenging problem in acoustic LWD technology. In this paper we propose a new method for separating tool waves from formation acoustic waves in acoustic LWD. This method is to measure the seismoelectric signal excited by the LWD acoustic waves. The LWD tool waves which propagate along the rigid tool rim can not excite any electric signal. This is due to the effectively grounding of the drill string during the LWD process makes it impossible to accumulate any excess charge at the conductive tool — borehole fluid interface. Therefore, there should be no contribution by the tool modes to the recorded seismoelectric signals. To theoretically understand the seismoelectric conversion in the LWD geometry, we calculate the synthetic waveforms for the multipole LWD seismoelectric signals based on Pride's theory [S. R. Pride, Phys. Rev. B, 50 (1994), pp. 15678-15696]. The synthetic waveforms for the electric field induced by the LWD-acoustic-wave along the borehole wall demonstrate the absence of the tool mode. We also designed the laboratory experiments to collect simulated LWD monopole and dipole acoustic and seismoelectric signals in a borehole in sandstone. By analyzing the spectrum of acoustic and electric signals, we can detect and filter out the difference between the two signals, which are the mainly tool modes and noise.